1982
DOI: 10.20506/rst.1.2.71
|View full text |Cite
|
Sign up to set email alerts
|

Hydatidosis in buffaloes in Bangladesh

Abstract: Four hundred and thirty-nine buffaloes of different age groups in Mymensingh, Bangladesh, were examined and 42.36% were found to be infected with hydatidosis. The infection was recorded in the liver 28.47%, lungs 32.80%, spleen 3.22%, heart 2.15%, kidney 1.08%, omentum 0.54%, and both liver and lungs 31.72%. The weak (78.40% and 81.25%), medium (15.20% and 11.11%) and heavy (6.40% and 7.64%) infections were recorded in the liver and lungs, res pectively. Cysts were fertile in 10. 34% of cases, sterile in 66.12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…In African countries, in north western Morocco the prevalence rate was 10.7, 1.4 and 80% in sheep, goats and camels respectively (Pandey et al, 1986); in Libya, the CE infection rate was reported to be 4.9% in sheep, 2.4% in goats, 2.7% in camels; and 15% in cattle (Kassem et al, 2013), while in Ethiopia, the prevalence rate was 35.15% in cattle, 11.78% in sheep, 4.9% in goats, 16.79% in camels, with pigs being free of the infection altogether (Fromsa and Jobre, 2011). In Egypt, the buffaloes in our study were likewise found to be free from any infection, which is in agreement with previous reports from Egypt (Rahman et al, 1992;Dyab et al, 2005), but in disagreement with reports from countries like Bangladesh, where 42.36% of the baffalo were found to be infected (Islam, 1982).…”
Section: Discusionsupporting
confidence: 83%
“…In African countries, in north western Morocco the prevalence rate was 10.7, 1.4 and 80% in sheep, goats and camels respectively (Pandey et al, 1986); in Libya, the CE infection rate was reported to be 4.9% in sheep, 2.4% in goats, 2.7% in camels; and 15% in cattle (Kassem et al, 2013), while in Ethiopia, the prevalence rate was 35.15% in cattle, 11.78% in sheep, 4.9% in goats, 16.79% in camels, with pigs being free of the infection altogether (Fromsa and Jobre, 2011). In Egypt, the buffaloes in our study were likewise found to be free from any infection, which is in agreement with previous reports from Egypt (Rahman et al, 1992;Dyab et al, 2005), but in disagreement with reports from countries like Bangladesh, where 42.36% of the baffalo were found to be infected (Islam, 1982).…”
Section: Discusionsupporting
confidence: 83%
“…Many researchers from various parts of the world have recorded different prevalences of CE in buffaloes. Epidemiological surveys have been conducted in Pakistan with prevalence rates ranging from 7.14 to 68% (Latif et al , 2010); in India with prevalence rates ranging from 3.81 to 69.0% (Irshadullah et al , 1989; Singh et al , 1989; Pednekar et al , 2009); in Nepal with a prevalence rate of 5% (Joshi et al , 1997); in Iraq with a prevalence rate of 6.57% (Al-Sultan & Jarjees, 1999); in Egypt with a prevalence rate of 0.46% (Haridy et al , 1998); in Italy with a prevalence rate ranging from 8.7 to 12.4% (Capuano et al , 2006; Cringoli et al , 2006) and in Bangladesh with a prevalence rate of 45.2% (Islam, 1982a, b).…”
Section: Discussionmentioning
confidence: 99%
“…In a 2010 study, the CE prevalence in slaughtered animals (cattle, sheep, and goats) was 26% in the Comilla (90 km from Dhaka) and Brahman Baria (100 km from Dhaka) regions of Bangladesh [6]. Additional studies have reported prevalences ranging from 17.2% to 29.6% in cattle [7][8][9]. A study of E. granulosus infection in stray dogs in Bangladesh revealed an average prevalence of 62.5%, with prevalences up to 75.8% recorded in dogs in and around slaughterhouses [5].…”
Section: Introductionmentioning
confidence: 99%